The effect of n-back training during hemodialysis on cognitive function in hemodialysis patients: a non-blind clinical trial - Yuta Noguchi; Marina Ito; Mai Mushika; Takuya Ito; Naoto Kawamura (Renal Replacement Therapy, 2020)
Abstract Background Traditional vascular risk factors such as hypertension, diabetes mellitus, hyperlipidemia, cigarette smoking, and cardiovascular disease with myocardial infarction and atrial fibrillation have been linked to cognitive impairment in patients with chronic kidney disease. Therefore, interventions for cognitive function that can be performed during hemodialysis are needed. In this regard, n-back training has been demonstrated to be effective in patients with cognitive impairment. Methods In this pre-post study, 12 patients underwent n-back training during hemodialysis. The patients, aged 52–80 years, had mild cognitive impairment and were tested before and after a 3-month training period. This study was carried out in a single dialysis center. The Mini-Mental State Examination, Montreal Cognitive Assessment-Japanese version, Benton Visual Retention Test, Trail Making Test, visual cancelation task, Symbol Digit Modality Test, and Paced Auditory Serial Addition Task were used as outcome measures. Results All patients completed the 3-month training program. Improvements were seen in scores for the Mini-Mental State Examination (P = 0.01), Montreal Cognitive Assessment-Japanese version (P = 0.01), Benton Visual Retention Test (P = 0.02), Trail Making Test-B (P = 0.01), and Paced Auditory Serial Addition Task 1 s (P = 0.01) and 2 s (P = 0.01) from baseline to 3 months. Conclusions Cognitive training during hemodialysis improved cognitive and attention function in patients with mild cognitive impairment. This suggests that the simultaneous provision of n-back training and hemodialysis can be effective for treating chronic kidney disease with cognitive impairment. Trial registration UMIN Clinical Trials Registry ( UMIN000033742 ); retrospectively registered on August 13, 2018.